Ways of improving dental structures from metal-free ceramics. Literature review - S. Nebogatov; L. Chulak (Kazimierz Wielki University, 2022)
Over the last 10 years, the use of zirconium dioxide ceramics as a framework material for the manufacture of microprostheses, single crowns and small bridges has increased. Their use in dental practice became possible with the help of CAD/CAM technologies. Clinical studies of ceramic restorations based on zirconium dioxide showed promising clinical results and high survival rates. However, chipping and fragility of ceramic masses layered on frameworks made of zirconium dioxide remains an actual and urgent problem of modern orthopedic dentistry. In modern global dental practice, layer-by-layer veneering on refractory models, CAD/CAM technology, and hot pressing techniques are used to achieve such results. In modern dentistry, the IRS e.max Press technologies occupy a rather significant place due to the simplicity and manufacturability of the process, but their use is restrained by the fear of orthopedists-dentists related to the fragility of metal-free structures and the complexity of clinical stages. Therefore, most often in case of destruction of the crown part of the tooth, metal hip inserts are used, the manufacturing technology of which continues to be improved. That is why in modern orthopedic dentistry, the problem of improving the quality of restoration of the frontal group of teeth by improving and approving the technology of pressed ceramics is urgent.